Preoperative serum albumin level as a predictor of perioperative outcome in patient undergoing major gastrointestinal surgery - Bhandari, Tika Ram; Shahi, Sudha; Bhandari, Ramesh Singh; Lakhey, Paleswan Joshi (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Hypoalbuminemia, as a marker of malnutrition and disease, is associated with higher risk of poor postoperative outcomes. However, no study has been reported from our country until now. Our aim was to identify the relationship between preoperative hypoalbuminemia and the development of complications after major gastrointestinal surgery. Methods: A prospective study of 106 patients who underwent major elective gastrointestinal surgery between July 2012 to June 2013 in Department of Surgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal were considered for the study. Serum albumin was determined preoperatively in all patients. Hypoalbuminemia was deﬁned as albumin less than 35 mg/dl. Thirty-day postoperative complications were analyzed. Results: The patients were 70 males (66 %) and 36 females (34%) with a mean age of 50 years (23-81). Thirty-six patients (34%) had hypoalbuminemia. Overall complication rate was 32%. Hypoalbuminemic patients had a significantly higher rate of postoperative complications (26.4 and 5.6%; P<0.05). In multivariate analysis, age (>50 year), BMI (<18 kg/m2), duration of surgery (>3 hours) and hypoalbuminemia (<35 mg/dl) were the significant risk factors for postoperative complications (P<0.05). Conclusion: Preoperative hypoalbuminemia is an independent predictor of postoperative outcomes in patients with elective major gastrointestinal surgery. Identification and optimization of nutritional status prior to surgery may improve surgical outcomes.